Ips Learning In Early Elementary School Grades In The Independent Curriculum - Restu Rahayu; Dhilla Pratiwi; Selvi Triwanvi; Ika Pra Sauma; Tin Rustini (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The importance of Social Studies (IPS) in elementary schools has been widely recognized, especially in facing the era of society 5.0. However, there are still challenges in students' understanding of IPS material. In this era, educators need to facilitate students to think critically, creatively, discuss, and work together in the context of social problems. IPS learning in elementary schools must adopt a constructivist approach and utilize methods such as design-based learning, project-based learning, cooperative-based learning, problem-based learning, and inquiry-based learning. This article outlines the importance of a new approach to IPS learning in elementary schools and evaluates five methods through a literature review. Building on previous research, this article presents a new perspective on the IPS approach that can improve student understanding and engagement in early grades.